Дослідження зміни якості моторних мастил при їх експлуатації в автобусах малої і середньої місткості - Сасов, О. О.; Коровкін, А. А. (НТУ "ХПІ", 2015)
Проведені теоретичні та експериментальні дослідження зміни якості моторних мастил при їх експлуатації в автобусах малої і середньої місткості які дозволяють прогнозувати термін експлуатації моторних мастил за його фактичним станом для підвищення ефективності експлуатації рухомого складу шляхом оптимізації строку заміни та раціонального використовування паливно-мастильних матеріалів. Зроблено висновки про те що строки заміни моторних мастил за пробігом або напрацюванням які рекомендує завод виробник не завжди достатньо обґрунтовані. Основні фізико-хімічні показники якості мастила не завжди досягають граничних значень до часу його зміни.

Theoretical and experimental studies of changes in the quality of motor oil in their operation in low and medium buses capacity have been conducted which let predict the lifetime of motor oil in its actual condition to improve operational efficiency of rolling stock by optimizing the replacement term and rational use of fuels and lubricants. Optimizing term of motor oils replacement essentially depends on their initial potential of physical and chemical properties and the rate of its depletion, conditions of buses exploitation and spoilage indicators of quality that reflect the actual state of lubrication during operation of the bus. Diagnosing the motor oil quality on the dielectric constant it can be asserted about the actual state of operated oil than about the mileage (km) or elaboration (hours). Knowing the limited and measured permeability of values we can predict another term of oil diagnosing or replacing. The conclusions have been made about the term of motor oils replacement for mileage or operating time recommended by the plant manufacturer is not always well-proved. Basic physical and chemical properties of oil quality do not always reach the limit values until it changes.
The research of quality change of motor oil during their use in buses of low and medium capacity
Keywords: ресурс двигуна; продукти зносу; діелектрична проникність; лужне число; life of the engine; engine oil; wear products; dielectric permeability; alkali number